2016
DOI: 10.1002/cctc.201600685
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective and Stable NiSn/SiO2 Catalyst for Isobutane Dehydrogenation: Effects of Sn Addition

Abstract: Ni/SiO2 catalysts with large surface area Ni particles exhibit high hydrogenolysis activity, leading to the formation of large amounts of methane and coke. To destroy the active sites for hydrogenolysis, namely the aggregated Ni ensembles, Sn species were introduced into the Ni/SiO2 catalyst. As expected, isobutene selectivity was significantly increased to 90.2 %. The promoting role of Sn on the dehydrogenation performance could be interpreted as both a geometric and electronic effect. On one hand, Sn additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 59 publications
(65 reference statements)
6
47
0
3
Order By: Relevance
“…(6)]. [38][39][40] However,h aving in mind the product ratios, it becomes evidentt hat further sources (precursors) for the methane formation must exist. Once formed, isobutane mayb ef ragmented into propene and methane [Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(6)]. [38][39][40] However,h aving in mind the product ratios, it becomes evidentt hat further sources (precursors) for the methane formation must exist. Once formed, isobutane mayb ef ragmented into propene and methane [Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Such fragmentation has been observed at high temperatureo ver solid materials. [38][39][40] However,h aving in mind the product ratios, it becomes evidentt hat further sources (precursors) for the methane formation must exist. For the liquid carbonyl compounds, formationb yk etonic decarboxylation was assumed as aw orking hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…Under these conditions, supported Ni catalysts are reduced to Ni 0 nanoparticles, which usually show poor stability, fast coke deposition, high methane selectivity, and low alkene selectivity . To improve the stability and selectivity, several Ni‐based catalysts have been studied, including NiSn, NiS, and NiP for the isobutane dehydrogenation reaction . NiAu bimetallic catalysts have been studied for the more challenging propane dehydrogenation reaction .…”
Section: Methodsmentioning
confidence: 99%
“…They suggested that the ligand and ensemble effects of P resulted in the low hydrogenolysis activity. Wang et al [19] studied the isobutane dehydrogenation over the NiSn/SiO 2 catalyst. They found that the addition of Sn effectively restrained the hydrogenolysis activity.…”
Section: Introductionmentioning
confidence: 99%